Câncer ginecológico em um estado do Nordeste do Brasil: análises de incidência, sobrevida e mortalidade - Silva, Brenda Evelin Barreto da (2024)
Background: Gynaecological cancers represent a global concern due to their impact on public health, resulting in thousands of deaths each year. Objectives: To analyse the trends in incidence and mortality of gynaecological cancers in Sergipe between 1996 and 2017, and to describe net survival estimates for cervical and ovarian cancers. Methods: This is a population- based study with data obtained from the Aracaju Cancer Registry and the Mortality Information System. Crude and age-standardised rates were calculated. Joinpoint analysis was used to identify changes in trends, calculating the annual percent change (APC) and the average annual percent change (AAPC). Net survival at one and five years after diagnosis was calculated using the Pohar Perme estimator and age-standardised with the weights of the International Cancer Survival Standards. Results: From 1996 to 2017, age-standardised incidence rates for gynaecological cancers showed a decreasing trend (AAPC: -3.1), while mortality rates increased (AAPC: 2.1). Cervical cancer showed an annual decrease in incidence (AAPC: -5.2) and a stationary trend in mortality rates (AAPC: 1.0). Incidence rates for vaginal cancer also decreased (AAPC: -5.5). Ovarian cancer saw an increase in mortality rates (AAPC: 3.9), as did uterine cancer (C54-C55; AAPC: 3.1). Vulvar cancer exhibited a substantial increase in mortality rates between 2001 and 2009 (APC: 27.1), followed by a decrease until 2017 (APC: -11.3). One-year net survival for cervical cancer decreased from 84.6% (1996-1999) to 73.4% (2015-2017), and five-year survival from 60.8% to 49.3% over the same period. Squamous cell carcinomas comprised 85.1% of cases and demonstrated comparable survival to adenocarcinomas. There was a decrease in age-standardised net survival at one and five years for squamous cell carcinoma over the years. One-year net survival for ovarian cancer varied between 60-70% and five-year survival between 31-47% during 1996-2017. Type I epithelial tumours accounted for 24.9% of cases and type II for 56.1%. One-year survival for both types was around 67-68.5%, but five-year survival was 32.5% for type II and 52% for type I. For type II tumours, one-year survival decreased from 75.9% (2000-2004) to 68.9% (2015-2017), while five-year survival increased from 26.7% to 37.2%. Conclusion: Although the incidence trends of gynaecological cancers have decreased, mortality rates have either increased or not significantly declined. Survival for cervical cancer has declined over the years, with no differences between squamous cell carcinoma and adenocarcinoma. For ovarian cancer, five- year survival has shown a slight increase. However, type II epithelial tumours have a lower five-year survival than type I. Despite advances in the diagnosis and treatment of gynaecological cancers, significant challenges remain in reducing mortality and improving survival.